Determination of Trace Metal Elements in Coastal and Estuarine Seawater by Polymer-Complexation-Ultrafiltration Technique and Inductively Coupled Plasma Mass Spectrometry - Lin, Ji-Jun; Duan, Hua-Ling; Gong, Zhen-Bin (Fēnxī huàxué, 2011)
A method using polymer-complexation and ultrafiltration for matrix modification and inductively coupled plasma mass spectrometry (ICP-MS) for determination of trace level of metal elements(Cu(2+), Pb(2+), Cd(2+), Ni(2+) and Ag(+)) in coastal and estuarine seawater has been developed. Full quantitative data collection mode and internal standard calibration curve were used for ICP-MS measurement. Under optimized conditions, the relative standard deviations (RSDs) were lower than 9.3% (0.20 mu g / L, n = 5), and the standard added recoveries were 78.7% - 95.2%. Detection limits (10 &) were from 1.2 ng / L(Cd) to 9.8 ng / L(Cu). The method blank ranged from 1.1 ng / L (Cd, Ag) to 9.1 ng / L (Cu). The developed method has been applied to simultaneously determine the metals in coastal and estuarine seawater.